Corrosion behavior of nickel plated low carbon steel in tomato fluid (2009)
"This research work investigated the corrosion resistance of nickel plated low carbon steel in tomato fluid. It simulated the effect of continuous use of the material in a tomato environment where corrosion products are left in place. Low carbon steel samples were nickel electroplated at 4V for 20, 25, 30 and 35 mins using Watts solution.The plated samples were then subjected to tomato fluid environment for for 30 days. The electrode potentials mV (SCE) were measured every day. Weight loss was determined at intervals of 5 days for the duration of the exposure period. The result showed corrosion attack on the nickel- plated steel, the severity decreasing with the increasing weight of nickel coating on substrate. The result showed that thinly plated low carbon steel generally did not have any advantage over unplated steel. The pH of the tomato solution which initially was acidic was observed to progress to neutrality after 4 days and then became alkaline at the end of the thirty days test (because of corrosion product contamination of the tomato)contributing to the reduced corrosion rates in the plated samples after 10 days. Un-plated steel was found to be unsuitable for the fabrication of tomato processing machinery without some form of surface treatment - thick nickel plating is suitable as a protective coating in this environment. "